Factors associated to the lack of condom use. Study in Chiclayo adolescents and young adults - Soto, Víctor (2006)
Objectives: To determine why Chiclayo district adolescents and young adults do not use condom and describe their sexual behavior main characteristics. Design: Transversal study, polyetapic sample. Setting: Chiclayo district, Peru. Patients: Three hundred and ninety-three adolescents and young adults, 196 of them females and 197 males. Interventions: Autoapplied questionnaire survey to adolescents and young adults in 2001. Chi square, odds ratio and logistic regression were used for statistical analysis. Main outcome measures: Condom use. Results: Time of first coitus differed, males being more precocious. Condom use in the past six months was minimum in both sexes, and the proportion of women who never used condom was high. Conclusions: Logistic regression analysis showed that the main associate factors for not using condom in males were unavailability, less pleasure and less love relationship; in women, loss of romanticism, interference with coitus, and use of other birth-control method.